Improved space charge transport model in bi‐layer dielectrics—considering carrier dynamic equilibrium. Issue 2 (11th February 2020) - Liang, Hucheng; Du, Boxue; Li, Jin; Yao, Hang; Wang, Zehua
Abstract : The Maxwell–Wagner model and bipolar charge transport model both aim at describing the charge transport behaviours in dielectrics. The Maxwell–Wagner model performs well in calculating the polarisation current and electric field distribution, but it is too macroscopic to describe the microscopic behaviours of space charges. The bipolar charge transport model can well simulate the space charge accumulation, but it cannot quantitatively relate the microscopic transport behaviours with the macroscopic conductivities of dielectrics. Considering the shortages of the above two models, an improved charge transport model, named carrier dynamic equilibrium model, was proposed in this study to simulate the polarisation process of the low‐density polyethylene/ethylene propylene diene monomer bi‐layer dielectric by introducing a source term of carrier dynamic equilibrium. Effects of carrier mobility and non‐equilibrium carrier lifetime on the simulation results were explored, and a comparison among the results of measurement and different models was also made. Compared with the Maxwell–Wagner model and bipolar charge transport model, the improved model has the best coincidence with measurements, which can provide an accurate reference for the design of high‐voltage direct current insulation systems.